Orp8 deficiency in bone marrow-derived cells reduces atherosclerotic lesion progression in LDL receptor knockout mice. - Erik van Kampen; Olivier Beaslas; Reeni B Hildebrand; Bart Lammers; Theo J C Van Berkel; Vesa M Olkkonen; Miranda Van Eck (PLoS ONE, 2014)
INTRODUCTION: Oxysterol binding protein Related Proteins (ORPs) mediate intracellular lipid transport and homeostatic regulation. ORP8 downregulates ABCA1 expression in macrophages and cellular cholesterol efflux to apolipoprotein A-I. In line, ORP8 knockout mice display increased amounts of HDL cholesterol in blood. However, the role of macrophage ORP8 in atherosclerotic lesion development is unknown. METHODS AND RESULTS: LDL receptor knockout (KO) mice were transplanted with bone marrow (BM) from ORP8 KO mice and C57Bl/6 wild type mice. Subsequently, the animals were challenged with a high fat/high cholesterol Western-type diet to induce atherosclerosis. After 9 weeks of Western-Type diet feeding, serum levels of VLDL cholesterol were increased by 50% in ORP8 KO BM recipients compared to the wild-type recipients. However, no differences were observed in HDL cholesterol. Despite the increase in VLDL cholesterol, lesions in mice transplanted with ORP8 KO bone marrow were 20% smaller compared to WT transplanted controls. In addition, ORP8 KO transplanted mice displayed a modest increase in the percentage of macrophages in the lesion as compared to the wild-type transplanted group. ORP8 deficient macrophages displayed decreased production of pro-inflammatory factors IL-6 and TNFα, decreased expression of differentiation markers and showed a reduced capacity to form foam cells in the peritoneal cavity. CONCLUSIONS: Deletion of ORP8 in bone marrow-derived cells, including macrophages, reduces lesion progression after 9 weeks of WTD challenge, despite increased amounts of circulating pro-atherogenic VLDL. Reduced macrophage foam cell formation and lower macrophage inflammatory potential are plausible mechanisms contributing to the observed reduction in atherosclerosis.